Prenatal diagnosis and molecular cytogenetic characterization of partial dup (18p)/del (18q) due to a maternal pericentric inversion 18 in a foetus with multiple anomalies - Emine Ikbal Atli; Engin Atli; Cihan Inan; Gülizar Fusun Varol; Cisem Mail; Esra Altan Erbilen; Sinem Yalcintepe; Selma Demir; Hakan Gurkan (Elsevier, 2022)
Objective: The 18q terminal deletion with inverted duplication is an extremely rare abnormality, with only three confirmed cases in Europe to date. Here, we report, for the first time, a case of de novo 18q inv-dup-del in a Turkish pregnant woman. Case report: A 30-year-old pregnant woman was referred for genetic analysis at her 25th gestational week due to foetal diaphragmatic hernia and rocker bottom feet. Cytogenetic analysis of the parents revealed a karyotype of 46,XX,inv(18) (p11.3q21.3) of the mother and a normal karyotype of the father. The foetal karyotype was defined as 46,XX,rec(18)del(18q)inv(18) (p11.3q21.3)mat. Conclusion: To our knowledge, this is the first report of a prenatal diagnosis. Genetic counselling issues for this family, particularly affected individuals, include an increased likelihood of reduced fertility and a risk of recurrence of parental inversion equal to 1/2 in surviving offspring.